215 Extent of Resection in Glioblastoma: Prognostic Validation of a New Classification from the RANO Resect Group. (April 2023) - Karschnia, Philipp; Young, Jacob; Ostorga, Antonio Gabriel Dono; Häni, Levin; Sciortino, Tommaso; Bruno, Francesco; Jünger, Stephanie T.; Teske, Nico; Morshed, Ramin A.; Haddad, Alexander F.; Zhang, Yalan; Stöcklein, Sophia; et al.
Abstract : INTRODUCTION: Terminology to describe extent of resection in glioblastoma is inconsistently applied. Based upon residual contrast-enhancing (CE) tumor, a surgical classification system was previously proposed. METHODS: The members of the RANO resect group retrospectively searched the databases from international seven neuro-oncological centers for newly diagnosed glioblastoma per WHO 2021 classification. Volumetric information (from pre- and post-operative MRI) and clinical data were collected. RESULTS: We identified 1021 patients with newly diagnosed glioblastoma. 744 IDHwt glioblastomas were treated with radiochemotherapy per EORTC 26981/22981 (TMZ/RT→TMZ) following surgery. Among such homogenously treated IDHwt patients, lower absolute residual tumor volumes (in cm 3 ) were superiorly associated with outcome. Accordingly, individuals with 'maximal CE resection' (class 2) had more favourable outcome compared to individuals with 'submaximal CE resection' (class 3) or 'biopsy' (class 4) (median OS: 19 versus 15 versus 10 months; p = 0.001). Additional resection of non-CE tumor (with ≤ 5 cm 3 residual non-CE tumor) translated into an additional survival benefit in patients with complete CE resection, thus defining class 1 ('supramaximal CE resection') (median OS: 24 versus 19 months; p = 0.008). The prognostic role of the resection classes was retained on multivariate analysis when adjusting for clinical and molecular markers. Notably, relative tumor reduction (in percentage) was not prognostic on multivariate analysis, and inter-rater agreement for CE and non-CE tumor on post-operative MRI was sufficient. CONCLUSIONS: The suggested "RANO categories for extent of resection in glioblastoma" are prognostic for outcome and may therefore be used for stratification of clinical trials. Removal of non-CE tumor beyond the CE tumor borders is associated with improved survival, providing a rationale to explicitly denominate such 'supramaximal CE resection'.